2019
DOI: 10.3847/1538-4357/ab1d52
|View full text |Cite
|
Sign up to set email alerts
|

A Limited Habitable Zone for Complex Life

Abstract: The habitable zone (HZ) is commonly defined as the range of distances from a host star within which liquid water, a key requirement for life, may exist on a planet's surface. Substantially more CO 2 than present in Earth's modern atmosphere is required to maintain clement temperatures for most of the HZ, with several bars required at the outer edge. However, most complex aerobic life on Earth is limited by CO 2 concentrations of just fractions of a bar. At the same time, most exoplanets in the traditional HZ r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 102 publications
(134 reference statements)
4
42
1
1
Order By: Relevance
“…The hypothesis presented in this paper is complementary to that espoused in Schwieterman et al (2019) in two respects. First, Schwieterman et al (2019) showed that CO 2 toxicity may move the outer edge of the HZ inward, as higher CO 2 concentrations can prevail at the outer edge, whereas this work suggests that O 2 toxicity might shift the inner edge of the HZ outward due to the higher XUV fluxes and abiotic buildup of O 2 .…”
Section: Prospects For Complex Lifesupporting
confidence: 53%
See 2 more Smart Citations
“…The hypothesis presented in this paper is complementary to that espoused in Schwieterman et al (2019) in two respects. First, Schwieterman et al (2019) showed that CO 2 toxicity may move the outer edge of the HZ inward, as higher CO 2 concentrations can prevail at the outer edge, whereas this work suggests that O 2 toxicity might shift the inner edge of the HZ outward due to the higher XUV fluxes and abiotic buildup of O 2 .…”
Section: Prospects For Complex Lifesupporting
confidence: 53%
“…First, Schwieterman et al (2019) showed that CO 2 toxicity may move the outer edge of the HZ inward, as higher CO 2 concentrations can prevail at the outer edge, whereas this work suggests that O 2 toxicity might shift the inner edge of the HZ outward due to the higher XUV fluxes and abiotic buildup of O 2 . Second, the analysis by Schwieterman et al (2019) indicates that the accumulation of CO (which is toxic to many metazoans on Earth) in atmospheres of M-dwarf exoplanets may render them uninhabitable, while this paper implies that exoplanets around M-dwarfs could become inhospitable to Earth-like biota because of their high XUV fluxes, which aid in abiotic O 2 buildup and cause O 2 toxicity in the process. Therefore, in a nutshell, CO 2 , CO and O 2 toxicity might jointly conspire to preclude complex Earth-like life on many M-dwarf exoplanets.…”
Section: Prospects For Complex Lifementioning
confidence: 88%
See 1 more Smart Citation
“…What time period is required for life to form and evolve? The ancient Earth was clearly not a place we would enjoy today, so long-term planetary environmental changes are important to understand as well (Schwieterman et al, 2019b). Such questions as these illustrate the strong relation of biology, astrobiology, and planetary science to exoplanet research.…”
Section: Habitable Environmentsmentioning
confidence: 99%
“…Recently, Schwieterman et al 14 used a 1-D radiative-convective climate model to argue that a HZ for complex life (e.g. animals and plants) would be significantly narrower than the classical main-sequence CO 2 -H 2 O HZ 1,3 .…”
mentioning
confidence: 99%